EFFECTIVENESS OF VETIVER GRASS (VETIVERIA ZIZANIOIDES L) IN REDUCING THE TOTAL SUSPENDED SOLID (TSS) CONTENT OF TOFU INDUSTRIAL LIQUID WASTE IN TOFU "X" BUSINESS IN PRABUMULIH CITY - Dara Veranika; Fera Meliyanti; Eko Heryanto (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2025)
The tofu industry has the potential to contribute liquid waste that can reduce water quality and cause water pollution, if the liquid waste is disposed of directly without prior treatment because it contains high organic pollutants. The purpose of this study was to determine the effectiveness of vetiver grass (Vetiveria Zizanioides L) in reducing Total Suspended Solid (TSS) levels in tofu industry liquid waste at the “X” tofu business in Prabumulih City in 2024. This type of research is experimental research on tofu factory liquid waste with the research design used is control group pre test -post test design. The population in this study was 30 liters of tofu industry wastewater. The sample in this study used the Grab Sampling technique. The results of the initial measurement of the tofu industry wastewater sample at the “X” tofu business, the TSS level was 259 mg/L. After the Phytoremediation process using Vetiver Grass (Vetiveria Zizanioides L) for 3 (three), 6 (six) and 9 (nine) days there was a decrease in TSS levels in the tofu industry wastewater. TSS levels decreased on day 3 with a TSS level value of 172.5 mg/L (33.4%), decreased on day 6 with a TSS level value of 101.7 mg/L (60.8%) and a very maximum decrease occurred on day 9 with a TSS level value of 66.3 mg/L. From the statistical test results of simple linear regression analysis, the sig probability value is 0.016. This proves that the length of time in the experiment using Vetiver Grass (Vetiveria Zizanioides L) has a sig probability value <0.05, . In conclusion, Vetiver Grass (Vetiveria Zizanioides L) is effective in reducing Total Suspended Solid (TSS) levels in tofu industry wastewater.